Anti-pest compounds from the volatile oil of Vitex negundo Linn - Dayrit, Fabian M (Archīum Ateneo, 1995)
During the course of research on botanical pesticides for small farmers, Vitex negundo, Linn (lagundi) was found to be a promising botanical insecticide. Laboratory tests of the volatile oils from the leaves of lagundi using Plutella xylostella, L. (diamondback moth) caused up to 83 percent mortality of the eggs in ovicidal tests and 91 percent mortality in the 3rd instar larvae in topical toxicity tests. Fractionation of the volatile oil and bioassay testing using diamondback moth led to the isolation and identification of Beta-endesmol as one of the components responsible for its ovicidal and topical toxicity. The chemical analysis of the volatile oil samples was carried out by GC/MS. Confirmation of the identity of Beta-eudesmol was done by IR, MS, and NMR analyses.